항산화제 Amifostine의 허혈 및 재관류시 흰쥐 적출심장의 심근 보호기능 - 허강배; 천수봉; 김송명 (Taehan Hyungbu Oekwa Hakhoe chi, 1998)
Background: S-2-(3 aminoprophlamino) ethylphosphorothioic acid(WR-2721) is one of the radical scavenging thiols. We tested its protective effects in the reperfused heart. Material and Method: The experimental setup was the constant pressure Langendorffs perfusion system. We investigated the radical scavenging properties of this compound in isolated rat hearts which were exposed to 20 minutes ischemia and 20 minutes reperfusion. Four experimental groups were used:group I, control, Amifostine 50 mg(1 mL) peritoneal injection 30 minutes before ischemia(group II), Amifostine 10 mg(0.2 mL) injection during ischemia through coronary artery(group III),and Amifostine 50 mg(1 mL) peritoneal injection 2 hrs before ischemia(group IV). The experimental parameters were the levels of latate, CK-MB, and adenosine deaminase(ADA) in frozen myocardium, the quantity of coronary flow,and left ventricular developed pressure, and it's dp/dt. Statistical analysis was performed using repeated measured analysis of variance and student t-test. Result: The coronary flow of group II and IV were less than group I and III at equilibrium state but recovery of coronary flow at reperfusion state of group II, III, and IV were more increased compared with group I. The change of systolic left ventricular devoloping pressure of group II and IV were less than control group at equilibrium state, which seemed to be the influence of the pharmacological hypotensive effect of amifostine. But it was higher compared with group I at reperfusion state. The lactic acid contents of group II were less than control group in frozen myocardium.(Group I was 0.20 0.29 mM/g vs Group II, which was 0.10 0.11 mM/g). The quantity of CK-MB in myocardial tissue was highest in group IV (P=0.026 I: 120.0 97.8 U/L vs IV: 242.2 79.15 U/L). The adenosine deaminase contents in the coronary flow and frozen myocardium were not significantly different among each group. Conclusion: Amifostine seemed to have significant cardioprotective effect during ischemia and reperfusion injuries of myocardium.